Pedagogical Renewal to Achieve Peace Education Curriculum: Artificial Intelligience as Path in Nigeria - Ojo, Erinsakin Martins; Damilola, Olaniyan Olaolu (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The study investigates pedagogical renewal to achieve a peace education curriculum through the integration of artificial intelligence (AI) in Nigerian universities. Despite the critical role of peace education in fostering national stability, traditional teaching methods often struggle to engage students effectively in the digital age. This study aimed to explore how AI can serve as a transformative path for pedagogical renewal in this field. A descriptive survey research design was employed, focusing on a population of peace education lecturers. Using a purposive sampling technique, a sample size of 180 respondents was selected. Data were collected via a self-structured instrument titled